(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: To describe the clinical and paraclinical characteristics of children over 5 years old diagnosed with pneumonia and positive for Mycoplasma pneumoniae by PCR at the Pediatric Center, Bach Mai Hospital. Subjects and methods: A descriptive study was conducted on 50 children diagnosed with pneumonia and confirmed positive for M. pneumoniae by PCR in nasopharyngeal samples, treated at the Pediatric Center, Bach Mai Hospital, from January 1, 2023 to December 31, 2023. Results: The highest proportion (84%) in the 6-11 years age group. The most common symptoms were cough (98%), fever (92%), tachypnea (58%). Among these, productive cough and fever were the most prevalent symptoms in the M. pneumoniae-positive pneumonia group, occurring in over 95% of cases. The most frequent physical examination findings included moist rans in the lungs (68%) and tachypnea (58%); less common findings were decreased breath sounds (32%), bronchial rans (6%), and chest retractions (2%). The lesions on X-ray were mainly localized lesions accounting for 62%. The severity of pneumonia with the pneumonia/severe pneumonia ratio was 7.3/1. Some factors related to pneumonia with PCR positive for M. pneumoniae were the average time from symptom onset to hospital admission, and the duration of fever in the group of pneumonia due to M. pneumoniae was longer than that of the group of pneumonia negative for M. pneumoniae. Conclusions: PCR-confirmed M. pneumoniae pneumonia was most commonly found in children aged 6-11 years. The predominant symptoms were cough, fever, moist rans in the lungs, and tachypnea. Chest X-ray findings primarily showed localized lung lesions.